15th AIAA/ISSMO Multidisciplinary Analysis and Optimization Conference 2014
DOI: 10.2514/6.2014-3274
|View full text |Cite
|
Sign up to set email alerts
|

Aerostructural optimization of the Common Research Model configuration

Abstract: The NASA Common Research Model (CRM) has become a standard test case for verification and validation of Reynolds averaged Navier-Stokes computational fluid dynamics codes. In this paper we evaluate the suitability of the CRM for aerostructural and aeroelastic optimization studies. Since the CRM was originally intended for aerodynamic studies only, the undeformed geometry is not available. To address this issue, we designed a jig shape and the corresponding wingbox structure for the CRM using an inverse design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 26 publications
1
71
0
Order By: Relevance
“…However, these studies did not consider dynamic gust loads or control effectiveness constraints. Indeed, Kenway et al [23] showed that the dynamic gust loads may become critical if the design is only optimized for maneuver cases. Up until the present time, mainly one-dimensional (spanwise) tow-steering have been considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies did not consider dynamic gust loads or control effectiveness constraints. Indeed, Kenway et al [23] showed that the dynamic gust loads may become critical if the design is only optimized for maneuver cases. Up until the present time, mainly one-dimensional (spanwise) tow-steering have been considered.…”
Section: Introductionmentioning
confidence: 99%
“…This framework has been used previously to perform aerostructural optimization of the uCRM geometry [7], as well as other investigations [9,10,11].…”
Section: Software Overviewmentioning
confidence: 99%
“…However, the undeformed jig shape is required for aerostructural optimization. To address this issue, Kenway et al [7] developed the uCRM using an inverse design procedure that minimized the L 2 norm of the geometric differences between the CRM and 1-g deflected uCRM. The wingbox used for the internal structure of the uCRM was designed with the intent to closely represent the analogous structure in a Boeing 777.…”
Section: A Ucrm Geometrymentioning
confidence: 99%
See 2 more Smart Citations